Single- and Dual-Band Bandpass Filters Using Coupled Stepped-Impedance Resonators With Embedded Coupled-Lines - He Zhu; Abbosh, Amin M. (IEEE microwave and wireless components letters, 2016)
A pair of coupled stepped-impedance resonators and its use to build single- and dual-band bandpass filter (BPF) is presented. To that end, two symmetrical stepped-impedance resonators with two embedded coupled-line sections are used. The adopted resonators are coupled at the two open-ended edges. The first even-mode resonant mode can be suppressed or excited based on whether it is required to realize a single- or dual-band response. Sharp passband selectivity and stopband harmonic suppression are achieved due to the existence of multiple transmission zeros. For verification, single- and dual-band filters using the proposed resonator are designed, fabricated and tested. The experimental results show a passband of 2.34-2.62 GHz (centered at 2.45 GHz for WLAN system), less than 1.5 dB insertion loss for the single-band filter; the dual-band design has two passbands ranged from 2.28-2.67 GHz and 3.35-3.63 GHz with less than 1.2 dB insertion loss for WLAN and WiMAX systems.